IN VITRO SUSCEPTIBILITY OF BORRELIA AFZELII, THE CAUSATIVE AGENT OF LYME BORRELIOSIS, TO THE SUPERNATANTS OF LACTIPLANTIBACILLUS PLANTARUM AND SACCHAROMYCES BOULARDII - Jevremović, Kristina; Kilibarda, Katarina; Božić, Dragana; Antić Stanković, Jelena; Nikolić, Biljana; Tomanović, Snežana; Veinović, Gorana (Srpski medicinski časopis Lekarske komore, 2025)
Introduction: Lyme borreliosis (LB) is a multisystem disorder caused by bacteria of the Borrelia burgdorferi sensu lato complex, transmitted to humans through the bite of Ixodes spp. ticks. Standard treatment typically involves prolonged antibiotic therapy. Currently, no topical product is available on the market for prophylactic use following a tick bite. Aim: The aim of the study was to investigate in vitro the effects of supernatants derived from the probiotic microorganisms Saccharomyces boulardii and Lactiplantibacillus plantarum, and their mixtures, on the growth and motility of Borrelia afzelii. Materials and methods: To test the susceptibility of Borrelia afzelii to probiotic microorganisms, a modified broth microdilution method adapted for Borrelia species was employed. Minimum inhibitory concentrations (MICs) were determined by evaluating both the number and motility of B. afzelii after 72 hours of incubation with supernatants under anaerobic conditions, compared to a positive control consisting of untreated B. afzelii culture.Results: The MIC was defined as the lowest concentration of the tested supernatant at which borrelia were non-motile and their number was reduced compared to the positive control. The following median MIC values were determined: 12.5% for S. boulardii, 6% for L. plantarum, and the lowest median MIC value of 0.8% was defined for the supernatant mixture of probiotic microorganisms.Conclusion: The mixture of Saccharomyces boulardii and Lactiplantibacillus plantarum exhibited the strongest inhibitory effect on the growth and motility of Borrelia afzelii. These results provide a foundation for further investigation into the molecular mechanisms of the inhibitory activity of probiotic microorganisms against Borrelia species.
Keywords: Lyme borreliosis; Borrelia afzelii; susceptibility; in vitro; probiotic microorganisms; minimum inhibitory concentrations